Analysis of Special Order Product Pricing Using a Relevant Cost Approach: A Case Study at Puna Jaya Tempe Factory, Poso Regency - Riski Kurniawati; Abdul Kahar; Sugianto Sugianto; Jurana Jurana (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This study aims to examine, analyze, and describe the determination of selling prices for special orders using the relevant cost approach and the cost-plus pricing method at "Puna Jaya" Tempeh Factory in Poso Regency. This research is a descriptive analytical study. The relevant cost analysis shows that the production cost for special-order tempeh is lower than regular production. The cost-plus pricing analysis indicates that the selling price of large special-order tempeh is 11.68% lower, while small special-order tempeh is 21.43% lower compared to regular production prices. Although the price of special-order tempeh is lower, it maintains profitability levels of 30.85% for large tempeh and 20.57% for small tempeh, consistent with regular production. This analysis is expected to contribute to "Puna Jaya" Tempeh Factory in enhancing its competitive advantage over other tempeh producers in Poso Regency.